Pyrolysis of Cyclohexane and 1-Hexene at High Temperatures and Pressures—A Photoionization Mass Spectrometry Study - Robert S. Tranter; Colin Banyon; Ryan E. Hawtof; Keunsoo Kim (Energies, 2023)
Cycloalkanes are important components of a wide range of fuels. However, there are few experimental data at simultaneously high temperatures and pressures similar to those found in practical systems. Such data are necessary for developing and testing chemical kinetic models. In this study, data relevant to cycloalkane pyrolysis were obtained from high repetition rate shock tube experiments coupled with synchrotron-based photoionization mass spectrometry diagnostics. The pyrolysis of cyclohexane was studied over 1270–1550 K and ~9 bar, while the more reactive primary decomposition product, 1-hexene, was studied at 1160–1470 K and ~5 bar. Insights into the decomposition of the parent molecules, the formation of primary products and the production of aromatic species were gained. Simulations were performed with models for cyclohexane and 1-hexene that were based on literature models. The results indicate that over several hundred microseconds reaction time at high pressures and temperatures the pyrolysis of cyclohexane is largely dominated by reactions initiated by cyclohexyl radicals. Furthermore, good agreement between the simulations and the experiments were observed for cyclohexane and 1-hexene with a modified version of the cyclohexane model. Conversely, the 1-hexene model did not reproduce the experimental observations.